Grinevich V. Feature of functioning of dialogs and monologues as fixed tongue assets of kinodramaturgii O. P. Dovzhenko - Grinevich V. (Philological Treatises, 2020)
This article deals with the investigation of the individual style of O.P.Dovzhenko’s film-dramatic art, in particular the peculiarities of dialogue and monologue function as main language means.